If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16(x + -9) = 4(2a + -1x) Reorder the terms: 16(-9 + x) = 4(2a + -1x) (-9 * 16 + x * 16) = 4(2a + -1x) (-144 + 16x) = 4(2a + -1x) -144 + 16x = (2a * 4 + -1x * 4) -144 + 16x = (8a + -4x) Solving -144 + 16x = 8a + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -144 + 16x + 4x = 8a + -4x + 4x Combine like terms: 16x + 4x = 20x -144 + 20x = 8a + -4x + 4x Combine like terms: -4x + 4x = 0 -144 + 20x = 8a + 0 -144 + 20x = 8a Add '144' to each side of the equation. -144 + 144 + 20x = 144 + 8a Combine like terms: -144 + 144 = 0 0 + 20x = 144 + 8a 20x = 144 + 8a Divide each side by '20'. x = 7.2 + 0.4a Simplifying x = 7.2 + 0.4a
| -6(u+6)=4u+4 | | 1/4t+3/5=2/5-t | | -7x+3-5x=-57 | | 8+28m-24-12m=0 | | -34=5x+3(x+2) | | f(x)=a(x+3)(x+1)(x-4) | | 5y-7x=12 | | 6x^2+3xy+3y^2=108 | | x=-1.5+0.5y | | -3t^2+16t-11=0 | | 16x^2+64t+64=0 | | 6-2x(3-12)=2x+90 | | 20x+5=-2x | | 3(u-5)-6u=-33 | | 0.4-8.1y-2.7y=1-10.8y-0.6 | | 11(k-2)+[k-3(k+1)]=0 | | (3c-8)(3c-8)=0 | | y=-3+2y | | 7(y+2)-5y=-4 | | 8-28m-24-12m=0 | | 2(t-1)+3t=2 | | -2(d+6)=-20 | | 2*j=25+j | | K-(-40)=32 | | 2t-4=2 | | 36=4(8x+1) | | 3(w+7)=-3 | | 8(1-4x)+8(x+3)=32 | | 8(1-4x)+8(m+3)=32 | | 4(0+1)=4(x+8) | | 22+2z=52 | | 9d+1=8d-18 |